Synthesis of Ultra-High molecular weight polyethylene elastomers by para-tert-Butyl dibenzhydryl functionalized α-Diimine nickel catalysts at elevated temperature. (5th September 2022) - Zhu, Ningning; Asadullah Khan, Muhammad; Pang, Wenmin; Behzadi, Shabnam; Qasim, Muhammad
Graphical abstract: Highlights: All catalysts were found highly active with maximum activity up to 7.04 × 10 6 g·mol −1 ·h −1 . The activity matches with the activity of high performance early transition metal catalysts. Thermal stability is a great issue of α -diimine based catalysts, which limits their application at industrial level. So in this perspective, all catalysts retain their considerable activity at elevated high temperature of 140 °C showing their good thermal stability whereas previously reported catalysts of this class usually decompose at 80 °C. Ultra-high molecular weight polyethylene is an emerging class of advanced materials. All the catalysts generate UHMWPE with maximum M n up to 333.4 × 10 4 g·mol −1 . All catalysts maintain generation of UHMWPE even at elevated temperature of 140 °C. Usually catalysts of this class generate high molecular weight polyethylene at low temperature, which limits their application for industrial level. The t -Bu rich nature and enables their good solubility in non-polar aliphatic hydrocarbons, which are industrially desired polymerization solvent. The catalysts generate polyethylene thermoplastic elastomers with great mechanical properties and strain recover (SR) values of up to 75%. Polymerization experiments have been carried out at small and large scale. The above mentioned properties make these catalysts highly attractive for industrial application. Abstract: The synthesis of polyethylene thermoplastic elastomers directly from ethylene as a feedstock is highly attractive in perception of their diverse applications and low cost. In this contribution, α -diimine nickel catalysts (Ni1-Ni4 ) with sterically bulky para - t -Bu dibenzhydryl moieties at ortho -position as well as different electron-donating and -withdrawing groups at para -position have been synthesized, characterized and applied for ethylene polymerization. These catalysts were found to be highly active with maximum activity up to 7.04 × 10 6 g·mol −1 ·h −1, producing polyethylene with ultra-high molecular weight of up to 333.4 × 10 4 g·mol −1 . More remarkably, these catalysts have thermal stability of up to 140 °C. The t -Bu rich nature enables their good solubility in non-polar aliphatic hydrocarbons, which are industrially desired polymerization solvents. Furthermore, these catalysts generate polyethylene thermoplastic elastomers especially at industrially high temperature of 140 °C, with great mechanical properties and strain recover (SR) values of up to 75 %. The properties including high thermal stability, polymerization in aliphatic hydrocarbons, and capabilities of yielding elastic ultra-high molecular weight polymers make them highly attractive for potential industrial applications.